2014
DOI: 10.1111/vop.12179
|View full text |Cite
|
Sign up to set email alerts
|

Corneal anesthesia following application of 0.4% oxybuprocaine hydrochloride ophthalmic solution to normal feline eyes

Abstract: This is the first study that provides objective information on the depth and duration of corneal anesthesia following instillation of oxybuprocaine in healthy feline eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
5
9
0
Order By: Relevance
“…As expected in this form of early‐onset glaucoma, mean corneal diameter was significantly larger in glaucomatous cats relative to normal cats, and in cats with FCG, larger corneal diameters correlated with decreased corneal sensitivity. Mean CTT was slightly lower in glaucomatous eyes relative to normal eyes; however, the difference was not statistically significant, and the values obtained in our study are generally similar to previously published ranges in normal cats . Similar findings were reported in prior studies involving human PCG patients .…”
Section: Discussionsupporting
confidence: 90%
“…As expected in this form of early‐onset glaucoma, mean corneal diameter was significantly larger in glaucomatous cats relative to normal cats, and in cats with FCG, larger corneal diameters correlated with decreased corneal sensitivity. Mean CTT was slightly lower in glaucomatous eyes relative to normal eyes; however, the difference was not statistically significant, and the values obtained in our study are generally similar to previously published ranges in normal cats . Similar findings were reported in prior studies involving human PCG patients .…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, the observation group required a shorter time for the onset of the anesthetic effect and the disappearance of pain, and a longer time for the recovery of pain sensation (P<0.01). The study by Giudici et al (21) indicated that following the combined application of procaine in epidural anesthesia, the time for the onset of the anesthetic effect and the disappearance of pain after anesthesia were shortened, and the recovery of pain sensation postsurgery was prolonged compared with the patients who were not administrated with procaine, which were consistent with the results of the present study. However, there are certain differences between the specific data of the two studies, which may be attributed to variation in the included subjects, the specific drug dose and the pain evaluation criteria.…”
Section: Time After Surgery -----------------------------------------supporting
confidence: 92%
“…2,3,20,21 It has been shown that oxybuprocaine and proxymetacaine produced corneal anesthesia in cats, 22,23 were more potent than bupivacaine or lidocaine in spinal anesthesia, 4 and were also more potent than bupivacaine on infiltrative cutaneous analgesia. 5 In the current experiment, oxybuprocaine and proxymetacaine were 30 and 50 times more potent than lidocaine as an infiltrative anesthetic.…”
Section: Discussionmentioning
confidence: 99%